Calprotectin as a New Sensitive Marker of Neutrophilic Inflammation in Patients with Bronchiolitis Obliterans - S. P. Jerkic; F. Michel; H. Donath; E. Herrmann; R. Schubert; M. Rosewich; S. Zielen (Mediators of Inflammation)
Introduction. Bronchiolitis obliterans (BO) is a chronic disease in which persistent inflammation leads to obstruction and obliteration of the small airways. The aim of this study was to evaluate the value of calprotectin as an inflammatory marker in induced sputum. Methods. Twenty-eight patients suffering from BO and 18 healthy controls were examined. Lung function was measured by spirometry, body plethysmography, and lung clearance index (LCI). The induced sputum was obtained, cell counts were performed, and cytokines were measured using cytometric bead array (CBA). Calprotectin was quantified in the sputum and serum samples using commercially available sandwich ELISA. Results. Spirometry parameters including forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1), and maximum expiratory flow rate at 25% vital capacity (MEF25) were significantly lower in BO patients than in healthy controls, whereas the reserve volume (RV), RV to total lung capacity ratio (RV/TLC), and LCI were significantly increased. In sputum, calprotectin levels, neutrophils, and IL-8 were significantly elevated. Calprotectin levels correlated strongly with IL-8 and other biomarkers, neutrophils FEV1 and MEF25. In serum, calprotectin was significantly diminished in BO patients compared to controls. Conclusion. Lung function is severely impaired in BO patients. Calprotectin is significantly elevated in the sputum of BO patients and reflects ongoing neutrophilic inflammation.